Strategy for strengthening disciplined character through holistic guidance: a phenomenological study of clients - Sudibja, Martina; Nurihsan, Juntika; Nurdin, Encep Syarief; Dahliyana, Asep; Ruyadi, Yadi; Hakam, Kama Abdul; Ganeswara, Ganjar Muhammad (Universitas Tanjungpura, 2026)
Discipline is an important character trait that enables humans to control themselves. However, many individuals still find it difficult to maintain consistent self-control, even though they have tried to be disciplined. The purpose of this study is to determine how to strengthen the character trait of discipline through holistic mentoring: a phenomenological study of clients. This study uses a qualitative approach with a phenomenological method. Data were obtained through in-depth interviews conducted with four clients who participated in the mentoring program. The analysis was conducted thematically to determine the meaning and importance of the participants' experiences. The results showed that holistic mentoring can improve discipline in three main ways: (1) internalization of values through personal reflection and interactive discussion, (2) increasing intrinsic motivation through spiritual and emotional approaches, and (3) creating behavioral consistency through practice and social support. The results of the study show the characteristics of discipline (a) responsibility for oneself, (b) responsibility for the family, (c) consistency and determination in the process, and (d) the ability to make wise decisions amid pressure, distractions, and the desire to do unproductive things. The results indicate that cognitive, affective, and spiritual aspects must be included in comprehensive and contextual coaching through moral guidance.